ANTIOXIDANT, ANTI-INFLAMMATORY, AND ANTIDIABETIC ACTIVITY OF HYDROALCOHOLIC EXTRACT OF OCIMUM SANCTUM: AN IN-VITRO AND IN-SILICO STUDY - Mehta, Vineet; Sharma, Arun; Kailkhura, Pallavi; Malairaman, Udayabanu (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Ocimum sanctum is known to be beneficial in the management of diabetes, however, its mechanism remains unexplored. This study was aimed to gain insite into the mechanisms through which it may counter diabetes and its complications. Methods: Hydroalcoholic whole plant extract of O. sanctum was screened for its antidiabetic potential and ability to counter oxidative and inflammatory stress through various in-vitro assays. Further, bioactive compounds that may be responsible for its antidiabetic activity were predicted through molecular-docking studies. Results: Crude extractive yield of 35.43% was obtained from Soxhlet extraction which mainly showed the presence of flavonoids, alkaloids, glycosides, and saponins. Plant extract showed good potential to scavenge 2,2-diphenyl-1-picrylhydrazyl free radical (40.95-68.71%) which may be attributed to its high phenolic (0.366 mg gallic acid equivalent/g) and flavonoid (0.113 mg quercetin equivalent/g) contents. Plant showed exceptional antiinflammatory activity which was evaluated through inhibition of protein denaturation (47.61-82.37%) and red blood cell membrane stabilization assay (43.66-78.28%). Further, extract treatment greatly inhibited Î±-glucosidase enzyme (34.17-71.45%) but failed to produce noticeable inhibition of Î±-amylase activity (1.94-14.88%). Docking studies predicted that rosmarinic acid, stigmasterol, linalool, bieugenol, and aesculin may be responsible for antidiabetic activity possessed by the plant through their interaction with the insulin receptor. Conclusion: These findings conclude that O. sanctum may be beneficial in managing diabetes and its associated complications through inhibiting Î±-glucosidase activity, reducing oxidative and inflammatory stress. Keywords: Diabetes mellitus, Ocimum sanctum, Antioxidant, Anti-inflammatory, Docking, Diabetic complications.